The Effect of Natural Collages on Fine Motor Skills in Children in Group B at Pembina Melati Tondo Public Kindergarten - Engel Zabrina Palit; Amrullah Amrullah; Sita Awalunisah; Besse Nirmala (Journal of Educational Sciences, 2026)
This study aims to determine the effect of natural material collage activities on the fine motor skills of children in group B at Pembina Melati Tondo State Kindergarten. The background of this study stems from the importance of early childhood education in optimizing all aspects of development, including fine motor skills. Collage activities using natural materials were chosen as a learning medium because they are believed to stimulate eye-hand coordination, finger strength, flexibility, and accuracy through activities such as sticking, arranging, and manipulating natural materials. This study used a quantitative approach with a quasi-experimental design of the one-group pretest-posttest type. There were 14 children in the study. Data were collected through observation, interviews, and documentation, then analyzed using descriptive analysis and the Wilcoxon Signed Rank Test non-parametric test. The results of the study showed an increase in fine motor skills after conducting natural material collage activities. The average score for children's abilities increased from 2.10 in the pretest to 3.14 in the posttest. The increase occurred in all aspects, namely strength, finger flexibility, and accuracy. The Wilcoxon test results showed a significance value of 0.005 (< 0.05), indicating a significant difference between the children's abilities before and after the treatment. Thus, collage activities using natural materials have been proven to have a significant and effective influence on improving the fine motor skills of early childhood.